2004
DOI: 10.1002/jsfa.1638
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrate/nitrite on the quality of sausage (sucuk) during ripening and storage

Abstract: The effects of nitrate/nitrite on the microbial and chemical properties and sensory quality of Turkish-style sausage (sucuk) were investigated during 15 days of ripening and 45 days of storage. Aerobic plate count, mould and yeast count, pH, 2-thiobarbituric acid value, residual nitrite level, nitrosomyoglobin conversion and sensory characteristics (flavour, colour and cutting scores) were monitored. Aerobic plate count increased (P < 0.05) during the first 8 days of ripening and decreased (P < 0.05) during fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
40
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 20 publications
14
40
0
Order By: Relevance
“…Cutting scores were evaluated as 1 that is not sliced, to 10 which is sliced perfectly. The overall sensory quality scores of sausages was determined from the same expression described by Bozkurt and Erkmen (2004) as:…”
Section: Sensory Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cutting scores were evaluated as 1 that is not sliced, to 10 which is sliced perfectly. The overall sensory quality scores of sausages was determined from the same expression described by Bozkurt and Erkmen (2004) as:…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…This can indicate that APC changed significantly with ripening time and addition of sage extract. Samelis et al, (1998);Bozkurt and Erkmen, (2004) found that APC increased during the ripening period and decreased during storage.…”
Section: Aerobic Plate Count (Apc)mentioning
confidence: 99%
“…19 A 2 g amount of homogenised sucuk sample was taken and TBARS were extracted twice with 10 mL of 0.4 mol L −1 perchloric acid.…”
Section: Determination Of Tbars Valuesmentioning
confidence: 99%
“…18 Commercially made sucuks are generally manufactured from a mixture of lamb and beef with tail fat, antimicrobials, antioxidants (nitrite/nitrate, ascorbic acid, α-tocopherol, phosphates), starter culture mixture and spices or spice oils (such as black pepper, red pepper, cumin, cinnamon, allspice and clove). 19 The sucuk dough is filled into artificial casing, fermented in controlled atmospheric conditions and heat treatment (about 60 • C for 1 h at 80% RH) is applied after the sucuks have been ripened in controlled atmospheric conditions (temperature and RH). 18 -20 The main physical, chemical and microbiological changes (texture, colour, flavour, odour, rancidity and biogenic amine formation) are mainly developed in the fermentation period.…”
Section: Introductionmentioning
confidence: 99%
“…The cutting score was evaluated by panellists assessing whether the bulgur-sucuk was easily cut or whether it stuck to the knife, on a scale from 10 (best) to 1 (worst). The overall sensory quality of bulgur-sucuks was calculated as follows: 28 overall sensory quality = (flavour × 0.5)…”
Section: Sensory Analysismentioning
confidence: 99%